Influence of the Manufacturing Parameter Error on Tooth Surface Error of curvic coupling - Wu Hongyan; Xu Guosheng; Zhao Hailong; Ma Qianshuai (Jixie chuandong)
To investigate the influence of manufacturing parameter adjustment errors of machine tool on the tooth surface geometrical precision of curvic coupling,the general tooth surface deviation equation which contained multiple processing parameter adjustment errors is inferred,and combined with two error index of tooth surface deviation（describe the deviation of theoretical offset tooth surface from standard one） and pitch deviation,the error analysis model of tooth surface geometry is constructed. With an example,the influence of manufacturing parameter adjustment error on tooth surface deviation and pitch deviation is analyzed,and the relational graph to describe its influence is drawn up.